Development of lectora inspire interactive media for video-based basketball learning: practical and effective - Oki Candra; Ahmad Rahmadani; Toktong Parulian; Anggara Oktaviandi; Rizki Pratama Khairullah (Journal Of Sport Education (JOPE), 2023)
(English)This research aims to determine the practicality of developing Lectoraspire interactive media in video-based basketball learning. This research uses quantitative descriptive, which describes the results of the questionnaire filled out by students. The population and sample of this research was class XI SMA Al Azhar Syfa Budi Pekanbaru II, totaling 45 people. This research procedure uses a questionnaire instrument with 4 indicators, namely material, learning media, use of learning media, and language. The instrument in this research uses a valid questionnaire involving various experts in the IT field, physical education teachers, and physical education lecturers. Instrument testing has been carried out involving similar samples. The data analysis technique uses quantitative descriptive techniques with percentages. Based on data analysis carried out in class XI SMA Al Azhar Syfa Budi Pekanbaru II, there was an average of 77.52% in the high category. The implications of this research can be used by physical education teachers and students, as an alternative learning. It is hoped that creativity and innovation will emerge for both educators and students in collaborating to achieve learning goals. Findings in the field explain that by implementing learning using Lectoraspire media, it is proven that many people are interested in learning basketball, and because of the unique content and innovation, students' imaginations develop so that students in the field can imitate or practice techniques correctly(Indonesian)Tujuan Penelitian ini untuk mengetahui praktikalitas pengembangan media interaktif lectora inspire pada pembelajaran bola basket berbasis video.  Penelitian ini menggunakan deskriptif kuantitatif, dimana mendiskripsikan hasil dari angket yang di isi oleh siswa.  Populasi dan sampel penelitian ini kelas XI SMA Al Azhar Syfa Budi Pekanbaru II yang berjumlah 45 orang. Prosedur penelitian ini menggunakan instrumen angket dengan 4 indikator yakni materi, media pembelajaran, penggunaan media pembelajaran dan bahasa dengan reliabelitas 0,679. Instrumen dalam penelitian ini menggunakan kuesioner yang sudah valid melibatkan berbagai pakar dibidang IT, guru pendidikan Jasmani, dosen Pendidikan Jasmani. Dan telah dilakukan ujicoba instrumen melibatkan sampel sejenis. Teknik analisis data menggunakan dengan teknik deskriptif kuantitatif dengan persentase.  Berdasarkan analisis data yang telah dilakukan pada kelas XI SMA Al Azhar Syfa Budi Pekanbaru II terdapat rata-rata 77,52% dengan kategori tinggi. Implikasi dalam penelitian ini bisa digunakan oleh guru pendidikan jasmani dan siswa, sebagai alternatif pembelajaran. Diharapkan nantinya muncul kreatifitas dan inovasi baik bagi pendidik maupun peserta didik dalam berkolaborasi mencapai tujuan pembelajaran. Temuan di lapangan menjelaskan bahwa dengan menerapkan pembelajaran menggunakan media lectora inspire terbukti banyak yang tertarik mempelajari bola basket dan karna keunikan konten, dan inovasi membuat imajinasi siswa berkembang sehingga siswa di lpangan bisa mencontoh atau mempraktekkan teknik dasar dengan benar.   Copyright © The Author (s) 2023Journal of Sport Education (JOPE) is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.